(RETRACTED) The development of Newton’s method by enhancing the starting point - Nabiyah, Ismi Ratin; Salim, Opim; Tulus, Tulus (SAINTIS Publishing, 2023)
Reason for Retraction (February 01st, 2024):This article has been retracted by the editors due to publication ethics misconduct by authors that the authors did not have ownership of the data that they report. Ismi Ratin Nabiyah as a corresponding Author of the article and as the representative of all authors, has asked the editor to retracted this article and recognize the mistakes for him.